Post-Esophagectomy Tube Feeding: A Retrospective Comparison of Jejunostomy and a Novel Gastrostomy Feeding Approach - Huang, Kenan (Public Library of Science, 2014)
BACKGROUND: McKeown-type esophagectomy combined with retrosternal reconstruction is a common surgical treatment for esophageal cancer. Various enteral feeding options are available post-esophagectomy, but no definitive preference exists. METHOD: “Retrosternal Route Gastrostomy Feeding (RGF)” was developed as an alternative enteral feeding approach that requires few additional surgical interventions. RGF is based on McKeown-type esophagectomy. We retrospectively compared RGF (n = 121) to jejunostomy feeding (JF) (n = 153) in 274 patients at the Department of Cardiothoracic Surgery in Changzheng Hospital (Shanghai, China) between June 2008 and Sept. 2012. Data pertaining to efficacy and procedural complications were compared among patients. RESULTS: RGF had a significantly shorter postoperative hospital stay (11 vs. 15 days, p<0.001) and time to removal of the feeding tube (9 vs. 14 days, p<0.001) compared to JF. Bowel obstruction (0.0% vs. 7.2% p = 0.003), abdominal distension (9.1% vs. 19% p = 0.022), and the occurrence of pneumonia (11.6% vs. 26.1% p = 0.003) were significantly lower in the RGF group. Feeding tube related complications and the associated morbidity rate were reduced in the RGF group. The two groups had similar tolerance to surgery. CONCLUSION: Our data suggests that RGF is a safe post-esophagectomy enteral feeding alternative to JF.